2018
DOI: 10.3390/su10092958
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Environmental Factors’ Impact on Donkeys’ Colostrum Quality

Abstract: Abstract:Colostrum is a natural product, issued by both mammals and humans in the first week of lactation. Among different species, donkey colostrum is considered to have, in addition to a valuable composition in nutrients and immune factors, an outstanding similitude with human colostrum. In this context, and taking into account the scarcity of available data concerning the interaction between climate factors and colostrum quality, a trial was conducted aiming to identify the possible influence of environment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Moreover, minimal concentration of Fe was observed in samples from Sălaj (0.71±0.02) and Bistrița-Năsăud (0.85±0.04), mg/l. Futhermore, resulted Fe values in breast milk are higher than concentrations reported in studies from Australia (Mohd-Taufek et al, 2016), Sweeden (Björklund et al, 2012), and Turkey (Altun et al, 2018), 47±99, 339±134 μg/l and 1.65±1.43 mg/l, respectively. (Mohd-Taufek et al, 2016;Björklund et al, 2012;Altun et al, 2018).…”
Section: Determination Of Minerals and Heavy Metalsmentioning
confidence: 63%
See 2 more Smart Citations
“…Moreover, minimal concentration of Fe was observed in samples from Sălaj (0.71±0.02) and Bistrița-Năsăud (0.85±0.04), mg/l. Futhermore, resulted Fe values in breast milk are higher than concentrations reported in studies from Australia (Mohd-Taufek et al, 2016), Sweeden (Björklund et al, 2012), and Turkey (Altun et al, 2018), 47±99, 339±134 μg/l and 1.65±1.43 mg/l, respectively. (Mohd-Taufek et al, 2016;Björklund et al, 2012;Altun et al, 2018).…”
Section: Determination Of Minerals and Heavy Metalsmentioning
confidence: 63%
“…Futhermore, resulted Fe values in breast milk are higher than concentrations reported in studies from Australia (Mohd-Taufek et al, 2016), Sweeden (Björklund et al, 2012), and Turkey (Altun et al, 2018), 47±99, 339±134 μg/l and 1.65±1.43 mg/l, respectively. (Mohd-Taufek et al, 2016;Björklund et al, 2012;Altun et al, 2018). The results regarding Zn concentrations are in concordance with Taufek et al ( 2016) that obtained similar concentrations of this element in milks samples (1390±211 µg/l).…”
Section: Determination Of Minerals and Heavy Metalsmentioning
confidence: 63%
See 1 more Smart Citation
“…According to different studies that have been conducted (Marchis et al., ; Salimei et al., ), jenny and mare colostrum have different composition. Mare colostrum has higher amount of lactose, which might affect sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that jenny colostrum added to an extender for freezing donkey semen yielded high sperm quality after thawing in comparison to egg yolk extenders (Álvarez, Luño, González, & Gil, ). We investigated if the addition of mare colostrum and jenny colostrum, which differ in their composition (Brumini, Criscione, Bordonaro, Vegarud, & Marletta, ; Marchis et al., ; Salimei et al., ), could have the same protective effect in donkey sperm cryopreservation.…”
Section: Introductionmentioning
confidence: 99%